Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting